2013
DOI: 10.1002/jgt.21736
|View full text |Cite
|
Sign up to set email alerts
|

Pebbling Graphs of Fixed Diameter

Abstract: Given a configuration of indistinguishable pebbles on the vertices of a connected graph G on n vertices, a pebbling move is defined as the removal of two pebbles from some vertex, and the placement of one pebble on an adjacent vertex. The m‐pebbling number of a graph G, πm(G), is the smallest integer k such that for each vertex v and each configuration of k pebbles on G there is a sequence of pebbling moves that places at least m pebbles on v. When m=1, it is simply called the pebbling number of a graph. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As a way to illustrate the techniques that are used to prove an asymptotic bound on the pebbling number for graphs of diameter four, we improve the O(n) term of Bukh's result to O(1). The general bound we obtain has been recently improved by Postle [], but we include it here as it briefly illustrates our technique for the diameter four case, which still is better than Postle's bound. Recall that a vertex is heavy if p(v)2d2, where d is the diameter of the graph.…”
Section: Asymptotic Resultsmentioning
confidence: 99%
“…As a way to illustrate the techniques that are used to prove an asymptotic bound on the pebbling number for graphs of diameter four, we improve the O(n) term of Bukh's result to O(1). The general bound we obtain has been recently improved by Postle [], but we include it here as it briefly illustrates our technique for the diameter four case, which still is better than Postle's bound. Recall that a vertex is heavy if p(v)2d2, where d is the diameter of the graph.…”
Section: Asymptotic Resultsmentioning
confidence: 99%
“…This completes the proof. ✷ showing that the pebbling bound for diameter 3 graphs given in [29] is tight.…”
Section: For Everymentioning
confidence: 98%
“…Aiming for tree-like structures (as was considered in [6]), one might consider chordal graphs of various sorts. Moving away from diameter 2, one might consider diameter 3 graphs; recently ( [29]), the tight upper bound of ⌊3n/2⌋ + 2 has been shown for this class. Combining these two thoughts we study split graphs in this paper, and find that their pebbling numbers can be calculated quickly, in fact, in O(n 1.41 ) time.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem.2.2. In (7), Postle [9]showed that if diameter d of a connected graph with n vertices is odd, then…”
Section: Lower and Upper Bounds Of Pebbling Number Of Watkins Snarkmentioning
confidence: 99%